Medication adherence: a review of pharmacy education, research, practice and policy in Finland - Bell JS; Enlund H; Vainio K (Centro de Investigaciones y Publicaciones Farmaceuticas, 2010)
Aims: To describe pharmacy education, research, practice and policy related to medication adherence in Finland since the year 2000.Methods: The three universities that provide pharmacy education (Åbo Akademi, University of Eastern Finland, and University of Helsinki) completed a structured pro-forma questionnaire regarding education related to medication adherence. A MEDLINE and EMBASE literature search was performed to identify English language peer-reviewed research that reported medication compliance, adherence or persistence. The Ministry of Social Affairs and Health was invited to nominate policies and documents related to medication adherence. A narrative review of medication counselling practices and professional service delivery through Finnish community pharmacies was undertaken.Results: Medication adherence was a theme integrated into obligatory and elective courses for bachelors and masters degree students. The literature search identified 33 English language peer-reviewed research articles reporting medication compliance, adherence or persistence published since the year 2000. Policy documents of the Ministry of Social Affairs and Health recognise that poor medication adherence may lead to sub-optimal treatment outcomes, and encourage patient participation in treatment decision making. Adherence practice in Finnish pharmacies has been strongly linked to the development of medication counselling services. Conclusions: Adherence research and education has focused on understanding and addressing the contextual factors that contribute to medication non-adherence. Adherence practice in community pharmacies has tended to focus on medication counselling and programs specific to particular disease states. Medication adherence is a topic that is integrated into courses for bachelor's and master's level pharmacy students in Finland.